2015
DOI: 10.1016/j.vaccine.2015.01.062
|View full text |Cite
|
Sign up to set email alerts
|

A gold glyco-nanoparticle carrying a listeriolysin O peptide and formulated with Advax™ delta inulin adjuvant induces robust T-cell protection against listeria infection

Abstract: In the search for an effective vaccine against the human pathogen, Listeria monocytogenes (Listeria), gold glyconanoparticles (GNP) loaded with a listeriolysin O peptide LLO91-99 (GNP-LLO) were used to immunise mice, initially using a dendritic cell (DC) vaccine approach, but subsequently using a standard parenteral immunisation approach. To enhance vaccine immunogenicity a novel polysaccharide adjuvant based on delta inulin (Advax™) was also co-formulated with the GNP vaccine. Confirming previous results, DC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 38 publications
3
64
0
Order By: Relevance
“…Vaccination of systemic listeriosis reduced IL-6 levels (Th2 pattern) and presented a significant increase in IL-12 levels (Th1 pattern) [11]. Here, we confirmed that neonatal listeriosis also caused MG to produce high levels of TNF-a (panel c, Figure 2) and IL-6 (Table 3), as reported in most neonatal human meningitis [1,29].…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Vaccination of systemic listeriosis reduced IL-6 levels (Th2 pattern) and presented a significant increase in IL-12 levels (Th1 pattern) [11]. Here, we confirmed that neonatal listeriosis also caused MG to produce high levels of TNF-a (panel c, Figure 2) and IL-6 (Table 3), as reported in most neonatal human meningitis [1,29].…”
Section: Resultssupporting
confidence: 87%
“…We have successfully developed dendritic cell vaccines loaded with LM peptides and deciphered that two peptides from this pathogen’s virulence factors, listeriolysin O (LLO) and glyceraldehyde-3-phosphate-dehydrogenase (GAPDH), LLO 91–99 and GAPDH 1–22 , conferred significant listeriosis protection in two mice models sensitive and resistant to listeriosis [8,9,10]. We have also prepared a gold glyconanoparticle (GNP) coupled to the LLO 91–99 peptide formulated with an adjuvant and achieved good vaccine effectiveness in adult mice [11]. Indeed, the application of nanotechnology in immunology is creating big expectations in the field of vaccination [12] and many examples of nanoparticles (NP) have appeared in the literature [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, DC or synthetic vaccines containing GADPH 1–22 epitopes and targeted to DC seemed to confer protection against experimental listeriosis, promoting Th1-Th17 and CD4 + -CD8 + T cell immune responses (20, 21, 30, 34). Here, we report that GAPDH 1–22 epitopes can activate MoDC of listeriosis patients with cancer receiving chemotherapy to release high levels TNF-α while low production of IL-6 and IL-10, a clear Th1 cytokine pattern.…”
Section: Discussionmentioning
confidence: 99%
“…16 They were therefore used to generate a Listeria based GNP nanovaccine by covalent linking of glucose and a peptide representing the Listeria T-cell epitope (LLO [91][92][93][94][95][96][97][98][99] ) to the GNP metallic core thereby creating GNP-LLO 91-99 nanoparticles. 17 The aim was to improve upon the effectiveness previously seen with a DC vaccine loaded with LLO 91-99 peptide that induced CD8 T-cell responses and IFN-g levels 6,9,18 but only modest Listeria protection. The GNP-LLO 91-99 nanovaccine was shown to be free of cytoxicity, effectively delivered the Listeria epitope to DC in vitro and in vivo and induced effective CD8 C T-cell immunity.…”
Section: Novel Nanoparticle Vaccines For Listeriosismentioning
confidence: 99%